2021
DOI: 10.1590/1518-8345.5353.3499
|View full text |Cite
|
Sign up to set email alerts
|

Dating violence among adolescents from a region of high social vulnerability

Abstract: Objective: to know and analyze the perceptions of adolescents with high social vulnerability regarding the establishment of dating violence. Method: a qualitative research study carried out with 19 adolescents from a central municipality São Paulo, Brazil. Data collection took place by means of focus groups and field diaries, with the data being analyzed thematically. Results: two categories emerged: “A new female posture in a context of traditional gender norms” and “Violence in intimate relationships: the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
1
0
2
Order By: Relevance
“…Un estudio cualitativo que objetivó conocer y analizar las percepciones de adolescentes de alta vulnerabilidad social frente a la construcción de relaciones de intimidad violentas identificó que las normas tradicionales de género aún ocupan un lugar importante en el delineamiento de las relaciones entre adolescentes. Tales comportamientos son más visibles en las relaciones de noviazgo, cuando el compromiso y la exclusividad se ven como características principales; además, los celos emergieron como el principal desencadenante de la violencia, y las tecnologías fueron los principales recursos contemporáneos para reforzarla (25) .…”
Section: Resultsunclassified
“…Un estudio cualitativo que objetivó conocer y analizar las percepciones de adolescentes de alta vulnerabilidad social frente a la construcción de relaciones de intimidad violentas identificó que las normas tradicionales de género aún ocupan un lugar importante en el delineamiento de las relaciones entre adolescentes. Tales comportamientos son más visibles en las relaciones de noviazgo, cuando el compromiso y la exclusividad se ven como características principales; además, los celos emergieron como el principal desencadenante de la violencia, y las tecnologías fueron los principales recursos contemporáneos para reforzarla (25) .…”
Section: Resultsunclassified
“…A qualitative study that aimed to understand and analyze the perceptions of highly vulnerable adolescents regarding the construction of violent intimate relationships, identified that traditional gender norms still play a key role in shaping adolescent relationships. Such behaviors are more visible in dating relationships, when commitment and exclusivity are seen as main characteristics; furthermore, jealousy emerged as the main trigger of violence, and technologies were the main contemporary tools to reinforce it 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Como características macrossistêmicas foram identificadas algumas crenças sobre os estereótipos e papéis tradicionais de gênero que parecem sustentar e justificar comportamentos não saudáveis em suas relações amorosas, percebidos como "proteção", "forma de amor" e "cuidado". 5 A reprodução de padrões sociais de gênero vulnerabiliza moças e rapazes de maneiras diferentes. Mesmo com algumas transformações ocorridas, parece ainda pesar sobre as mulheres a ideia do comportamento recatado e mais reservado como algo de relevância para a concretização do namoro ou escolha da parceria amorosa, aspecto observado nesta pesquisa.…”
Section: Atravessamentos De Gênerounclassified
“…A Organização Mundial da Saúde (OMS) 1 considera a VN como uma forma precoce de violência entre parceiros íntimos, com as primeiras experiências acontecendo entre 11 e 17 anos de idade. A VN entre adolescentes pode ocorrer de diversas formas, sendo comum as tipologias: psicológica, digital, física, sexual, perseguição (stalking) e financeira, 2,4,5 ilustradas pela Figura 1 com base no Centers for Disease Control and Prevention (CDC). 2 A VN pode ocorrer de forma face a face (off line) e/ou mediada pela Internet (on line).…”
Section: Introductionunclassified